2021
DOI: 10.3390/s21062125
|View full text |Cite
|
Sign up to set email alerts
|

Observation Quality Assessment and Performance of GNSS Standalone Positioning with Code Pseudoranges of Dual-Frequency Android Smartphones

Abstract: The new generation of Android smartphones is equipped with GNSS chips capable of tracking multi-frequency and multi-constellation data. In this work, we evaluate the positioning performance and analyze the quality of observations collected by three recent smartphones, namely Xiaomi Mi 8, Xiaomi Mi 9, and Huawei P30 pro that take advantage of such chips. The analysis of the GNSS observation quality implies that the commonly employed elevation-dependent function is not optimal for smartphone GNSS observation wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Previous studies have found that the data quality of GPS and Galileo L5/E5 frequency is better than L1/E1 [ 22 , 23 , 24 ], and the use of L1/E1 and L5/E5 dual-frequency data can effectively weaken ionospheric delay. However, due to the fact that the number of dual-frequency data obtained by the smartphone is small, the utilization rate of the dual-frequency data is low.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies have found that the data quality of GPS and Galileo L5/E5 frequency is better than L1/E1 [ 22 , 23 , 24 ], and the use of L1/E1 and L5/E5 dual-frequency data can effectively weaken ionospheric delay. However, due to the fact that the number of dual-frequency data obtained by the smartphone is small, the utilization rate of the dual-frequency data is low.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They also investigated the performance of single point positioning using the Galileo E5a pseudorange observations compared with those of the E1 signal. Robustelli et al (2021) then assessed the quality of the smartphone observations. The results indicated a low C/N 0 dependence on satellite elevation and a clear azimuthal asymmetry of signal gain.…”
Section: Absolute Positioningmentioning
confidence: 99%
“…also suggested a C/ N 0 weighting model instead of an elevation-dependent weighting model. Employing the C/N 0 weighting model instead of an elevation-dependent weighting model has been also reported byBanville et al (2019),Liu et al (2019),Paziewski et al (2019) andRobustelli et al (2021).…”
mentioning
confidence: 97%
“…Nowadays, the global positioning system (GPS), in a coded solution, is the primary method of position determination in modern air (Lachapelle et al., 1996; Ochieng et al., 2003; Brodin et al., 2005; Krasuski et al., 2020; Krasuski and Savchuk, 2020), land (Ojeda and Borenstein, 2007; MacLean, 2009; Naranjo et al., 2009; Zandbergen and Barbeau, 2011; Sun et al., 2017; Merry and Bettinger, 2019; Elhajj and Ochieng, 2020; Robustelli et al., 2021) and marine (Grant et al., 2009; Han et al., 2016; Ramesh et al., 2016; Bhatti and Humphreys, 2017; Glomsvoll and Bonenberg, 2017) navigation. Its use depends primarily on the positioning accuracy, which has been constantly changing over the last years, hence GPS applications depend on the current positioning accuracy of that system (Rudnicki and Specht, 2016; Specht, 2019). For this reason, it is important to determine the current GPS accuracy because it is decisive for the possibilities of using the system in various navigation applications.…”
Section: Introductionmentioning
confidence: 99%